The influence of intraoral devices on dynamic performance of golf athletes : a pilot study - Chéroux, Vera (2019)
Abstract of the poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Campus Egas Moniz, Monte de Caparica, Portugal